Interaction and innovation: practical strategies for inclusive consumer-driven research in health services. Issue 12 (16th December 2019) - Dahm, Maria R; Brown, Anthony; Martin, Dean; Williams, Maureen; Osborne, Brian; Basseal, Jocelyne; Potter, Mary; Hardie, Rae-Anne; Li, Julie; Thomas, Judith; Georgiou, Andrew
Abstract : Introduction: Despite advances in the co-creation of clinical research involving consumers in the last few decades, consumer engagement in health services research generally remains inconsistent and is too often treated as a perfunctory exercise. Objective: Drawing on a health services study on diagnostic test result management, communication and follow-up, we: (1) outline practical strategies used to enhance the contribution of health consumer representatives across all stages of health services research, including active involvement in prioritising objectives for data analysis and participating in data analysis and the dissemination of findings; and (2) describe the impact of continued engagement of consumers on the programme of research, the interpretation of findings and their translational potential. Key innovations: Key enabling innovations for engagement included: (1) planned opportunities for long-term consumer involvement across all stages of the research process from conception to dissemination; (2) enhanced consumer engagement capacity; (3) purposeful recruitment of appropriately trained consumers; (4) provision of support structures for active consumer involvement in research design, analysis and write-up; and (5) financial support for consumer involvement. Impact/Conclusion: Enhancing consumer contribution and establishing inclusive research design requires a negotiated, interactive, meaningful and transparent process. As a collaborative approach, consumer-driven research involvement offers opportunities for new, often unexpected or unexplored perspectives to feature across the whole research process. In a move away from tokenistic consumer involvement, consumers and researchers who participated in this novel and immersive research project identified inclusive research as a powerful tool to enhance health services research and its translation into effective policy.